Малі аномалії розвитку: їх особливості при деяких мультифакторіальних захворюваннях - Дємєнкова, І.Г. (Фактори експериментальної еволюції організмів, 2014)
Aim. To identify quantitative and qualitative character of small developmental anomalies (SDA) in multifactorial diseases. Methods. 119 adolescents with the hypothalamic syndrome of puberty (gr. I), 43 children, whose parents had experienced radiation impact in childhood and adolescence, owing to the Chernobyl disaster (gr. II), 41 childrenunder 3 yrwith an impaired psychomotor development (gr. III), and 60 children of the control group took part in the study. The authors used the scheme, developed in the department of clinical genetics and ultrasound diagnosis of Kharkiv Medical Academy of Postgraduate Education (KMAPЕ), Merks H.M. classification. Results. More than 6 SDA have been registered in the examined children. A higher SDA concentration in the cranio-facial area has been revealed in the patients from gr. II and gr. III. Conclusions. More than 6 SDA have been registeredin our patients significantly more often, an average level of stigmatization (7-10 SDA) has been observed mainly in children of the groups under investigation. The revealed spectrum of SDA can testify to the congenital or acquired defects in collagen biosynthesis, and, as a consequence, to the connective tissue dysfunction.